(untitled) (New York, 1995)
This pocket-sized compendium on the pathophysiology, signs and symptoms, diagnosis and management of all disorders offers synoptic coverage, an outline format and abundant use of tables and charts summarize key clinical points so the reader can get to the information quickly. Each chapter is page-referenced to the 13th edition of "Harrison's Principles of Internal Medicine". This edition features extended coverage of AIDS and HIV, women's health and infectious disease. It also features new material on peptic ulcers.
Keywords: Internal medicine,Nội khoa; Handbooks, manuals, etc.,Sổ tay, hướng dẫn sử dụng, vv